Superresolution under Photometric Diversity of Images. (5th June 2007) - Gevrekci Gevrekci, Murat Murat; Gunturk Gunturk, Bahadir K. Bahadir K.
Abstract : Superresolution (SR) is a well-known technique to increase the quality of an image using multiple overlapping pictures of a scene. SR requires accurate registration of the images, both geometrically and photometrically. Most of the SR articles in the literature have considered geometric registration only, assuming that images are captured under the same photometric conditions. This is not necessarily true as external illumination conditions and/or camera parameters (such as exposure time, aperture size, and white balancing) may vary for different input images. Therefore, photometric modeling is a necessary task for superresolution. In this paper, we investigate superresolution image reconstruction when there is photometric variation among input images.